The Potential of Online Tasks to Facilitate Autonomous Language Learning with the Use of Online Dictionaries in a Higher Education ESP Classroom - Carolina Girón-García (Revista Alicantina de Estudios Ingleses)
The use of Information and Communication Technologies (ICTs) and previous studies in lexicography have shown the frustration that many students experience with the amount of information to which they are exposed to solve terminological doubts in the field of English for Specific Purposes (ESP). Yet, ICTs can prepare the ground for learning inside and outside the classroom. The incorporation of technological tools together with the use of integrated resources in Task-Based Language Teaching (TBLT) learning tasks provide multiple benefits in the field of ESP, as well as greater motivation and autonomy. This study aims at shedding new light on the ability of Higher Education (HE) students to (a) learn content and vocabulary with the use of online dictionaries and other online resources in a Legal English course; (b) foster motivation to perform an online task (OT); (c) develop autonomy; and (d) build new knowledge. To achieve this aim, the present study used a mixed-methods approach (i.e., qualitative and quantitative data) and was developed in two stages: (1) Creation and design of the online task (i.e., Lesson integrated into a Moodle platform); design of three questionnaires administered before and after the experiment; and implementation of the OT with university students (N=171) enrolled in a Legal English course; and (2) collection of data and analysis. The results acknowledged the success rates in terms of achievement (i.e., experimental group). The conclusions indicated that this OT had been valuable to students to learn specialised vocabulary and content, as well as to know how to use an online dictionary effectively. The OT design in this research adds value to previous studies’ existing weaknesses in dictionary training. As a result, this OT provides learners with training in the use of online dictionaries, which improves their autonomous language learning.